Revisiting the Principles of International Contracts in the Digital Trade Era: Towards a Global Legal Framework - Hidayati, Sri; Susilowati, Etty; Akkapin, Supaphorn (Journal Evidence Of Law, 2025)
Digital commerce has fundamentally transformed the legal foundations of classical international contracts in several ways. Principles such as consensualism, freedom of contract, and good faith face serious challenges due to the emergence of algorithmic contracts, power asymmetries on digital platforms, and the complexity of cross-border jurisdictions. This study critically examines the normative limitations of existing legal frameworks, including the CISG, UNIDROIT Principles, and UNCITRAL Model Laws, when confronted with a digitalized contractual environment. Using a normative-comparative approach, this study redefines contractual principles by incorporating concepts such as algorithmic fairness, digital accountability, and trust-by-design. This study emphasizes that the global legal order for digital contracts must transcend the nation-state paradigm and shift toward a pluralistic, principle-based framework through transnational legal processes. This study contributes to the development of legal theory and regulatory design by proposing a roadmap for an inclusive and adaptive global normative architecture.